A Novel Picture Fuzzy n-Banach Space with Some New Contractive Conditions and Their Fixed Point Results. (25th September 2020) - Asif, Awais; Aydi, Hassen; Arshad, Muhammad; Ali, Zeeshan
Abstract : A picture fuzzy n -normed linear space (N PF ), a mixture of a picture fuzzy set and an n -normed linear space, is a proficient concept to cope with uncertain and unpredictable real-life problems. The purpose of this manuscript is to present some novel contractive conditions based on N PF . By using these contractive conditions, we explore some fixed point theorems in a picture fuzzy n -Banach space (B PF ). The discussed modified results are more general than those in the existing literature which are based on an intuitionistic fuzzy n -Banach space (B IF ) and a fuzzy n -Banach space. To express the reliability and effectiveness of the main results, we present several examples to support our main theorems.